The availability of controlled vocabulary to users for information retrieval - Cruz, Maria Carolina Andrade e [UNESP]; Ferneda, Edberto [UNESP]; Fujita, Mariangela Spotti Lopes [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2022)
The controlled vocabularies are normally used in indexing, in the process of standardization of concepts for the representation of information, acting as a mediating agent between the natural language contained in documents and the language of the information system. However, controlled vocabularies can also favor the search for information from their availability to the user, considering that this would contribute to the user's autonomy in the information retrieval process, considering that libraries can make this resource available in the online catalog where searches are performed based on the initiative and needs of users. Thus, previous research on the use of controlled vocabularies in university libraries is rescued, and we highlight the question related to the presence of the vocabulary in the online catalog for the user's use, in which 39 libraries state that they use controlled vocabularies in the indexing process and 18 of them make the resource available in the online catalog. Objective: With this, the proposed objective is to investigate the controlled vocabularies present in the catalogs of the participating libraries and analyze their availability, that is, how they are presented to the users. Methodology: Exploratory research from the analysis in online catalogs of university libraries. Results: The research recognized the presence of controlled vocabularies in 16 distinct catalogs, in which authority list (11 libraries), thesaurus (4) and subject heading list (1) were found. Conclusion: Considering the 39 libraries that have controlled vocabularies for indexing, only 16 libraries (16) made some available to the user. However, for these libraries or for others besides those analyzed in this research, we suggest a better presentation of the vocabularies in the catalogs, since they may go unnoticed because they are not easily visible to the user. In addition, users should be provided with tutorials on how to use them so that they can get to know the resource and improve the searches performed in the catalog.
Keywords: Controlled vocabulary; Information retrieval; Information search; Online catalog